The court of the stone children - Cameron, Eleanor 1912- (New York Puffin Books, 1990)
Aided by the journal of a young woman who lived in nineteenth-century France, Nina solves a murder mystery dormant since the time of Napoleon.
First published in the United States by E.P. Dutton ... 1973"--T.p. verso.
Keywords: Space and time -- Fiction; Mystery and detective stories